2019
DOI: 10.1111/phpp.12520
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the phototoxicity induced by BRAF inhibitors and alleviation through antioxidants

Abstract: Background Small molecules tackling mutated BRAF (BRAFi) are an important mainstay of targeted therapy in a variety of cancers including melanoma. Albeit commonly reported as side effect, the phototoxic potential of many BRAFi is poorly characterized. In this study, we evaluated the phototoxicity of 17 distinct agents and investigated whether BRAFi‐induced phototoxicity can be alleviated by antioxidants. Methods The ultraviolet (UV) light absorbance of 17 BRAFi was determined. Their phototoxic potential was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Phototoxicity is a common adverse event of vemurafenib (up to 52% of patients) but less frequent with dabrafenib and encorafenib (1%-3%). 4,20,21 Clinically, it presents as an immediate sensation of heat and burning on sun exposure and solar urticaria-like erythema (without pruritus). 5,21 Patients also develop a delayed sunburn-like reaction that can range from mild erythema (Fig.…”
Section: Phototoxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Phototoxicity is a common adverse event of vemurafenib (up to 52% of patients) but less frequent with dabrafenib and encorafenib (1%-3%). 4,20,21 Clinically, it presents as an immediate sensation of heat and burning on sun exposure and solar urticaria-like erythema (without pruritus). 5,21 Patients also develop a delayed sunburn-like reaction that can range from mild erythema (Fig.…”
Section: Phototoxicitymentioning
confidence: 99%
“…21 UVA irradiation of BRAFi produces a UVA-absorbing photoproduct that might be responsible for photosensitivity. 20 Studies also suggest that vemurafenib has an inhibitory effect on UV-induced DNA damage repair. 20 In addition, vemurafenib also inhibits ferrochelatase, resulting in elevated protoporphyrin levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SK channels have been implicated in diverse physiological functions such as synaptic enhancement and long¬ term potentiation. Apamin injections accelerate acquisition of the bar-pressing response and also accelerate bar-pressing rates [149,150]. Wasp and honey bee and hornet toxin peptides because convulsions due to presence of albumin a rigid octadecapeptide but it is no longer be considered an exclusive neurotoxin.…”
Section: Therapeutic Usesmentioning
confidence: 99%
“…It has been pointed out that the reactive metabolites may be responsible for direct or indirect toxicity to cellular proteins or DNA; however, the underlying mechanisms remain unclear (Parham et al 2016;Spraggs et al 2011). Moreover, it makes sense to investigate the ability of LAP to induce photosensitivity reactions bearing in mind that BRAF (serine/threonine-protein kinase B-Raf) inhibitors show a considerable phototoxic potential after exposure to UVA light (Heppt et al 2020). Besides, it has been reported that afloqualone, a quinazoline-marketed drug, causes photodermatosis as a side effect (Tokura et al 1994).…”
Section: Introductionmentioning
confidence: 99%